2008
DOI: 10.1002/chem.200701425
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective CC Bond Formation to Sulfonylimines through Use of the 2‐Pyridinesulfonyl Group as a Novel Stereocontroller

Abstract: Enantioselective CC bond formation to 2‐pyridinesulfonylimines afforded products with good enantioselectivity. Dynamic induction of chirality on the sulfur by coordination of a chiral Lewis acid to the pyridine nitrogen and one of the prochiral sulfonyl oxygens induces enantioselectivity. Since the 2‐pyridinesulfonyl group can easily be removed after the reaction, it acts not only as an activating group but also as an efficient stereocontroller.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 101 publications
1
20
0
Order By: Relevance
“…The latter reagent is also used for removal of the trifluoromethanesulfonyl protective group. The deprotection of the 2 pyridinesulfonyl protective group is usually achieved in yields higher than 90% using Mg in acetic acid [35] or methanol [36] at 0°C. The mesyl protective group is also removed under reducing conditions by treatment with LiAlH 4 or Na/ t BuOH, HMPA/NH 3 [3], while the PhSH/K 2 CO 3 system in DMF shows good results for the deprotection of the p nitrobenzenesulfonyl group [37].…”
Section: N Sulfonyl Imines (Ii)mentioning
confidence: 99%
“…The latter reagent is also used for removal of the trifluoromethanesulfonyl protective group. The deprotection of the 2 pyridinesulfonyl protective group is usually achieved in yields higher than 90% using Mg in acetic acid [35] or methanol [36] at 0°C. The mesyl protective group is also removed under reducing conditions by treatment with LiAlH 4 or Na/ t BuOH, HMPA/NH 3 [3], while the PhSH/K 2 CO 3 system in DMF shows good results for the deprotection of the p nitrobenzenesulfonyl group [37].…”
Section: N Sulfonyl Imines (Ii)mentioning
confidence: 99%
“…We selected cobalt, [10] which is homologous with rhodium but a more abundant first-row transition metal, [11] and investigated the ability of high-valent cobalt catalysts to promote CÀH bond functionalization. Optimization studies with 2-phenylpyridine (2 a) and the sulfonyl imine 3 a [12][13][14] as model substrates are summarized in Table 1. Several commercially available Co II and Co III salts showed no catalytic activity at 100 8C in 1,2-dichloroethane ( Table 1, entries 1 and 3-5).…”
mentioning
confidence: 99%
“…A catalytic amount of Lewis basic bidentate phosphine oxide 1 effectively activated and modified the properties of Brønsted basic rare-earth metal aryloxide catalysts, switching the diastereoselectivity from syn to anti in the lanthanum-catalyzed direct Mannich-type reaction. The mechanistic studies, a preliminary trial in a catalytic asymmetric reaction, and the extension of the Lewis base/Brønsted base catalysis to Michael and nitroaldol reactions are also described.We recently reported an iPr-pybox/La(OAr 1 ) 3 (Ar 1 = 4-MeO-C 6 H 4 ) complex which catalyzed the syn-selective direct asymmetric Mannich-type reactions [7] of imines 2 [8] with trichloromethyl ketone 3 a, an ester donor equivalent (Table 1, entry 1). [9,10] During the mechanistic studies of the reaction, we found that the reaction did not proceed with either La(OAr 1 ) 3 alone (Table 1, entry 2,) or iPr-pybox alone (Table 1, entry 3).…”
mentioning
confidence: 99%
“…We recently reported an iPr-pybox/La(OAr 1 ) 3 (Ar 1 = 4-MeO-C 6 H 4 ) complex which catalyzed the syn-selective direct asymmetric Mannich-type reactions [7] of imines 2 [8] with trichloromethyl ketone 3 a, an ester donor equivalent (Table 1, entry 1). [9,10] During the mechanistic studies of the reaction, we found that the reaction did not proceed with either La(OAr 1 ) 3 alone (Table 1, entry 2,) or iPr-pybox alone (Table 1, entry 3).…”
mentioning
confidence: 99%
See 1 more Smart Citation